The Use of Pretend Play and Drawings to Explore Children’s Social Representations About Learning and Teaching English - Cadavid Múnera, Isabel Cristina; Vásquez García, Juan Carlos; Botero Mejía, Juan David (Íkala, Revista de Lenguaje y Cultura, 2015)
<!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--> <!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--> <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Research with and for children is a subject that has not been widely explored within the field of foreign language teaching and learning in our context. In this article, we present the reasons, data collection instruments (drawings and pretend play) and the analysis processes involved in our research project called “La mirada de los niños y las niñas sobre la enseñanza y el aprendizaje del ingles” in which we learned about children’s social representations concerning learning and teaching English. We finally concluded that research that considers children as participants, not as objects of a study, implies the design and implementation of data collection instruments that coherently respond to the children’s affective, cognitive and social characteristics. Children’s voices have usually been left out of the decision making processes concerning educational policies, hence more research of this kind is needed in order to include their perspective about the strengths and weaknesses of the educational environment they are immersed in. <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->